Bhārate jātīya āndolana, bā, jātiya abhibyakti, Kamgresa, Svadesi-āndolana, asahayoga, biplabāda, Khilāphat, o prabāsi Bhāratabāsira itihāsa - Mukhopādhyāya, Prabhātakumāra, 1892- (Baradā Ejensi, 1925)
History of freedom-movement in India.